2015
DOI: 10.1063/1.4915125
|View full text |Cite
|
Sign up to set email alerts
|

3C-SiC/ZnS heterostructured nanospheres with high photocatalytic activity and enhancement mechanism

Abstract: 3C-SiC/n-type ZnS heterostructured nanospheres synthesized hydrothermally deliver enhanced photocatalytic performance under visible light excitation. The heterostructured catalysts consisting of 3C-SiC and ZnS nanocrystals with a mean size being less than 5 nm exhibit extended light absorption to the visible range. The proper band structure of the 3C-SiC and ZnS nanocrystals and intrinsic electric field induced by the heterojunction promote separation of photoexcited electrons and holes in the ZnS and 3C-SiC n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
3
8
0
Order By: Relevance
“…The solutions were kept overnight in the dark before illumination. To make our results comparable with the literature data, we synthesized ZnS NPs and a ZnS/SiC NP composite according to ref using 10 mL of SiC-I solution for the ZnS/SiC composite. The average size of ZnS NPs is 3.5 nm; however, they form aggregates with about 100 nm diameter …”
Section: Experimental Sectionsupporting
confidence: 55%
See 1 more Smart Citation
“…The solutions were kept overnight in the dark before illumination. To make our results comparable with the literature data, we synthesized ZnS NPs and a ZnS/SiC NP composite according to ref using 10 mL of SiC-I solution for the ZnS/SiC composite. The average size of ZnS NPs is 3.5 nm; however, they form aggregates with about 100 nm diameter …”
Section: Experimental Sectionsupporting
confidence: 55%
“…A study on electrochemical hydrogen evolution using SiC NPs showed that thin films containing SiC NPs in the range of 3–8 nm have exceedingly high efficiency when used for water splitting, while larger particles (20 nm) show negligible effect. The sensitizer property of SiC NPs with a diameter of about 4 nm was studied on ZnS/SiC heterostructures . SiC NPs enhanced the photocatalytic efficiency of ZnS as demonstrated in a dye degradation study.…”
Section: Introductionmentioning
confidence: 99%
“…The main reason for this is the rapid recombination of the photoinduced electron-hole pairs in SiC photocatalysts [39,40]. Therefore, various engineering strategies, including the formation of unique SiC nanostructures (e.g., quantum dots [41], nanoparticles [42], nanowires [43], and hollow spheres [44]), construction of heterostructures (e.g., SiC-TiO2 [45], SiC-ZnS [46], SiC-MoS2 [47], SnO2-SiC [48,49], and SiC-CdS [50]), hybridization of SiC with metal co-catalysts (e.g., SiC-Pt [43], SiC-IrO2 [51]), and nanocarbon materials (e.g., SiC-graphene [52,53]), have been employed to promote the performance and durability of SiC photocatalysts since the initial research on water splitting in 1990 [54]. Further investigations show that the SiC-graphene nanoheterojunction with intimate interfacial contacts between SiC and graphene exhibits enhanced photoactivities for water splitting owing to the improved charge separation resulting from the formation of Schottky-junction interfaces [55].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] SiC nanoparticles have shown additional properties due to size confinement effects, which allows for the creation of nanocomposites in new applications. [5][6][7][8] In particular, SiC nanoparticles with average sizes below 10 nm present quantum confinement effects and thus can be designed for semiconductor-based violet light sources because of their good stability and high optical band gap. [9][10][11] Various routes have been proposed for the synthesis of SiC nanoparticles over the last decade, including carbothermic reduction, 12 chemical vapor deposition (CVD), [13][14][15] ball milling, 16 laser ablation, 10 thermal/nonthermal plasma process, [17][18][19][20] and electrochemical/chemical etching.…”
Section: Introductionmentioning
confidence: 99%
“…SiC nanoparticles have shown additional properties due to size confinement effects, which allows for the creation of nanocomposites in new applications 5‐8 . In particular, SiC nanoparticles with average sizes below 10 nm present quantum confinement effects and thus can be designed for semiconductor‐based violet light sources because of their good stability and high optical band gap 9‐11 .…”
Section: Introductionmentioning
confidence: 99%